Immunohistologic Detection of Estrogen and Progesterone Receptors on Paraffin Blocks of Breast Cancer: Correlation with Histological and Cytological Grade (TAJ: Journal of Teachers Association, 2019)
Breast cancer is the second common cause of cancer death in women of our country. Treatment of breast cancer depends on a number of parameters known as pathological and biological prognostic markers. Knowledge of the tumour grade would avoid under treatment of high grade carcinomas and over treatment of low grade carcinomas. Out study evaluated the feasibility of a grading system on FNA of duct cell carcinoma (NOS) and its ability to predict the histologic grade of the surgical specimens. The two widely practice grading system; Robinson’s cytological grading and Scraff Bloom Richardson histological grading system were utilized for this purpose. Various reports quote varied reproducibility, ranging from 50 to 90% correlation between histologic and cytologic grade. In this study, the correlation between histologic and cytologic grade is 86.3%. In this study association between grading by FNAC and histology was statistically highly significant (χ2=27.66, df=1, p